Case 3746: Ripiphoridae Laporte, 1840 and Ripiphorus Bosc, 1791 (Insecta, Coleoptera): proposed conservation of usage by designating Ripiphorus subdipterus Fabricius, 1792 as the type species of Ripiphorus and proposed ruling that Laporte (1840) used the type genus Ripiphorus in the sense defined by the type species Ripiphorus subdipterus - Bousquet, Yves; Bouchard, Patrice (Bulletin of Zoological Nomenclature, 2018)
The purpose of this application, under Articles 65.2.2 and 81.1 of the Code, is to conserve the current usage of the generic name Ripiphorus Bosc, 1791 and the familygroup name Ripiphoridae Laporte, 1840. The current usage of Ripiphorus is threatened by the discovery that its first valid type-species designation is Mordella paradoxa Linnaeus, 1760 which would result in Ripiphorus being the valid name for the species currently included in Metoecus Dejean, 1834 and Myodites Latreille, 1819 being the valid name for the species currently placed in Ripiphorus. In addition, the current usage of Ripiphoridae would be threatened because of the altered concept of its type genus. In order to avoid nomenclatural instability we propose that Ripiphorus subdipterus Fabricius, 1792 be designated as the type species of Ripiphorus and that the Commission rule that Laporte (1840) used Ripiphorus in the currently-accepted sense.
Keywords: Nomenclature; taxonomy; RIPIPHORIDAE; Arion lusitanicus; Ripiphorus subdipterus